Tibiofemoral Osteoarthritis and Varus-Valgus Laxity - Freisinger, Gregory M. (J Knee Surg, 2016)
The purpose of this study was to systematically review and synthesize the literature measuring varus-valgus laxity in individuals with tibiofemoral osteoarthritis (OA). Specifically, we aimed to identify varus-valgus laxity differences between persons with OA and controls, by radiographic disease severity, by frontal plane knee alignment, and by sex. We also aimed to identify if there was a relationship between varus-valgus laxity and clinical performance and self-reported function. We systematically searched for peer-reviewed original research articles in PubMed, Scopus, and CINAHL to identify all existing literature regarding knee OA and objective measurement of varus-valgus laxity in vivo. Forty articles were identified that met the inclusion criteria and data were extracted. Varus-valgus laxity was significantly greater in individuals with OA compared with controls in a majority of studies, while no study found laxity to be significantly greater in controls. Varus-valgus laxity of the knee was reported in persons with OA and varying degrees of frontal plane alignment, disease severity, clinical performance, and self-reported function but no consensus finding could be identified. Females with knee OA appear to have more varus-valgus laxity than males. Meta-analysis was not possible due to the heterogeneity of the subject populations and differences in laxity measurement devices, applied loading, and laxity definitions. Increased varus-valgus laxity is a characteristic of knee joints with OA. Large variances exist in reported varus-valgus laxity and may be due to differences in measurement devices. Prospective studies on joint laxity are needed to identify if increased varus-valgus laxity is a causative factor in OA incidence and progression.